MINING LAW & REGULATORY: PRACTICE IN INDONESIA - Hayati, Tri (Indonesia Law Review, 2016)
Mining law, since before the Indonesian independence has already been a debatable topic between the business sector, Government, and other stakeholders until now. Several issues of mining law that have been debated among others, are: the form of concession and the authority for issuing mining licenses in relations with the right of state control stipulated under Article 33 paragraph (3) of the 1945 Indonesian Constitution, issues regarding taxes and royalties, environmental issues and other obligations. Since the enactment of Indische Mijn Wet 1899 until the enactment of Law No. 4 of 2009, these debates have yet to be settled; more, other serious issues are rising. These issues are steeply raised since the beginning of the reformation era of Local Governance which was marked by the enactment of Law No. 22 of 1999 that gives the power for the Municipal/City level Government to regulate the mining sector.